The Air Lubrication Behavior of a Kingsbury Thrust Bearing Demonstration - Wanjun Xu; Jiangang Yang (International Journal of Rotating Machinery)
In order to understand the air lubrication behavior of Kingsbury thrust bearing demonstration, an experimental and theoretical investigation on a simulated Kingsbury thrust bearing was presented. The motions of the thrust disk and tilting pads were measured by eddy current sensors for three mass load cases. A simplified theoretical model governing the motion of the thrust disk was established. The bearing successfully passed the examination of lamp extinction and maintained the maximum rotation time of 16 s. The effective hydrodynamic film with a thickness of about 5 μm was concentrated on the middle region of the working surface under a flatness of 0.010 mm. The adverse effect of the three surface bumps was minimized by the swing motion of tilting pads. Moreover, about 1/3 air film thickness was shown to be wasted due to the surface irregularity. However, the requirements of surface quality and misalignment were appropriately relaxed through the design of the centrally pivoted tilting pads. This design is conducive to thin-film lubrication and is a potential application for microturbines.